2009
DOI: 10.1007/s10522-009-9244-0
|View full text |Cite
|
Sign up to set email alerts
|

c-myb has a character of oxidative stress resistance in aged human diploid fibroblasts: regulates SAPK/JNK and Hsp60 pathway consequently

Abstract: This study examined whether c-myb acts as a survival molecule in aged cells. A previous in vitro ageing model suggested that aged cells have a higher cell capacity for survival after exposure to oxidative stress, which involves blockage of the translocation of Hsp60 from the mitochondria to the cytoplasm followed by SAPK/JNK inactivation, than young cells. In human diploid fibroblasts (HDFs), c-myb expression increased gradually with ageing, and this increase had a significant influence on the cell survival ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Here, the 25 transcripts associated to disease-specific CpG sites were enriched for transcription factor binding sites for MYB ( z -test; TRANSFAC: FDR < 0.05), a transcription factor associated to aging, 15 including the response to oxidative stress of aged cells 16 . It is of note that the DNA polymerase POLD3 is among the MYB targets, whose deregulation, due to its DNA repair activity, might have a direct impact on the disease phenotypes as it was observed for the DNA repair gene WRN (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Here, the 25 transcripts associated to disease-specific CpG sites were enriched for transcription factor binding sites for MYB ( z -test; TRANSFAC: FDR < 0.05), a transcription factor associated to aging, 15 including the response to oxidative stress of aged cells 16 . It is of note that the DNA polymerase POLD3 is among the MYB targets, whose deregulation, due to its DNA repair activity, might have a direct impact on the disease phenotypes as it was observed for the DNA repair gene WRN (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…23 However, it was demonstrated that c-myb increases the cell viability and decreases the apoptosisrelated signalling activation in the ageing process of human diploid fibroblast cell. 18 This shows that c-myb plays a critical role in cell proliferation or survival under inflammatory condition. Furthermore, c-myb has been shown to be essential for the proliferation and survival of human leukemia cells.…”
Section: Discussionmentioning
confidence: 96%
“…A series of studies was performed on the role of c‐myb in stress‐induced cell ageing, which also is a cause of inflammation . However, it was demonstrated that c‐myb increases the cell viability and decreases the apoptosis‐related signalling activation in the ageing process of human diploid fibroblast cell . This shows that c‐myb plays a critical role in cell proliferation or survival under inflammatory condition.…”
Section: Discussionmentioning
confidence: 99%
“…Senescent fibroblasts have been reported to resist apoptosis by the up-regulation of a number of anti-apoptotic genes such as survivin [6], c-myb [7], major vault protein [8], and Bcl-2 [9,10]. However, whether epigenetic mechanisms control the expression of pro- and anti-apoptotic genes in senescent fibroblasts have not been defined.…”
Section: Introductionmentioning
confidence: 99%